AML evolution from preleukemia to leukemia and relapse. Issue 2 (June 2015) - Shlush, Liran I.; Mitchell, Amanda
Abstract: Dismal outcomes of acute myeloid leukemia (AML), especially in the elderly, are mainly associated with leukemia relapse and primary no response to initial therapy. This review will focus on AML relapse, and how a better understanding of the evolutionary stages that lead to relapse might help us improve disease outcome. The fact that the relapse rate for some AMLs is so high indicates that we do not truly understand the biology of relapse or possibly that we are not implementing our current understanding into, clinical practice. Therefore, this review will also aim to explore some of the current understanding of AML relapse biology in order to identify the gaps in our knowledge and translation. Accumulating evidence suggests that the root of relapse evolves even before the time of diagnosis, meaning that the complex clonal structure of AML is created before patients present to the clinic. Some of the clones that exist at diagnosis can survive chemotherapy and give rise to relapse. Accordingly, in order to better understand the mechanisms of relapse, we must consider both early and late steps in AML evolution.